Interrogation in Wolof : two strategies and a puzzle for wh-question words - (:unkn) unknown (My University, 2013)
Wolof (Niger-Congo, Senegal) makes a typologically interesting use of noun class markers in its constituent question (or wh-question) words. As in other languages with noun class systems, the nominal lexicon is distributed into classes governing characteristic agreement schemes. In Wolof, the ten class agreement morphemes take the form of a bound consonantal morpheme C- : k-, b-, g-, j-, w-, m-, s-, l- (for singular), and ñ-, y- (for plural). The class agreement morphemes are used to form grammatical noun modifiers (mostly postposed to the noun modified) such as the definite and indefinite articles (as examplified in 1) and, demonstratives, quantifiers and relative pronouns. To the set of noun class morphemes should be added the two adverbial classifiers for space (f-) and manner (n-) which take the same suffixes as the noun class markers.(1)(a)nitk-i ‘the person close to the speaker’(b)nitñ-i ‘the people close to the speaker’(c)xajb-i ‘the dog close to the speaker’(d)xajy-i‘the dogs close to the speaker’These noun class morphemes are also used to form interrogative proforms, e.g. k-an ‘who?’, f-an ‘where?’, b-an xaj ‘which dog?’. The wh-question words formed with noun class markers are actually organized into two parallel sets according to a general pattern whereby a common interrogative morpheme is affixed to different noun class markers. Across the two sets, the same class consonants are used as a base to which a common interrogative stem, either −an or −u, is suffixed. These two parallel sets of interrogative pronouns and pronominal adverbs trigger different verb inflections: the Null Tense conjugation for the –u set and one of the three focusing conjugations for the –an set, as illustrated in (2) and (3):(2)F-anladëkk?where1COMPFOC3SGliveWhere does he live? (3)F-umudëkk?where2NULL3SGliveWhere does he live?The existence of this dual system is quite puzzling at first since the two patterns for content question
Keywords: African Research